Mapping the infotainment literature: current trajectories and suggestions for future research. Issue 1 (2nd January 2020) - Marinov, Robert
ABSTRACT: Academic interest in what has been termed "infotainment" has grown considerably since the term was coined in the 1980s. Today, the burgeoning field of infotainment research has become an important interdisciplinary field of study producing numerous political, cultural, and social insights. Nevertheless, infotainment remains highly contested, multifaceted, and incoherent, both as a term and a field of study. Preliminary attempts have been made to give greater conceptual clarity and standardization to the term, although their success has been limited, leaving difficulties in analyzing and comparing findings in a unified manner. In this review essay I outline the findings from a comprehensive literature review by delineating three mains trajectories of infotainment research: (1) research on soft news programming; (2) research on traditional news media; and (3) research on media systems and global infotainment. To conclude, I offer three suggestions for future infotainment research, arguing that scholars should attempt to achieve standardization and conceptual clarity within, rather than across research trajectories, that political theory should be more explicitly incorporated into the literature for the purposes of standardizing methods and clarifying normative debates, and that research should also focus on the synergies between contemporary trends in political campaign/communications strategies and trends in infotainment.